STRATEGI PEMBANGUNAN EKONOMI BERBASIS SISTEM AL-MAQASHID - Asmuni Asmuni (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
The economic crises are occurred not only in the developing countries, but also in the developed ones. The signals provide a strong approval that economic based on capitalism and socialism has failed to create prosperity and to humanize the human-being themselves. Furthermore, Moslem countries which are the victims of both capitalism and socialism are getting sufferer, since they are trapped on foreign loan with high interest accumulation. Consequently, those Moslem countries cannot develop themselves, for their natural resources are more given to the developed countries as compensation and investment. The remaining is for foreign loan payment and is often corrupted. If collaboration is established based on a mutual interest, foreign hegemony towards the developing countries is not occurred. From this point, it is important to develop economy using the maqashid system which is planning and involving the substantial problem. The system proposes the investment loan must be used to develop productive sectors, such as infrastructure and facilities of education and training in order that the society has skill to live independent, and capable to improve their prosperity.